Sustainable development goals through Islamic education: a literature review - Elihami, Elihami; Pajarianto, Hadi (Journal of Education and Learning (EduLearn), 2025)
The essay delves into the complex interrelationship between Islamic education and the sustainable development goals (SDGs), intertwining environmental awareness, social justice, and ethical ideals derived from Islamic teachings. By investigating the potential and problems at this juncture, it emphasizes the need for a comprehensive strategy to incorporate SDGs into Islamic education. The article provides solutions for educators and policymakers to bridge the gap between these two domains, nurturing a generation with Islamic values and a deep understanding of sustainable development. This is achieved through a thorough review of the literature, identifying emerging themes that will shape the future of Islamic education policy. These themes include the integration of environmental principles, innovative pedagogies, international collaboration, and a focus on inclusive education.